2003
DOI: 10.1089/153036603768395799
|View full text |Cite
|
Sign up to set email alerts
|

Detection of West Nile Virus Infection in Birds in the United States by Blocking ELISA and Immunohistochemistry

Abstract: A blocking ELISA targeting an immunodominant West Nile epitope on the West Nile Virus NSI protein was assessed for the detection of West Nile-specific antibodies in blood samples collected from 584 sentinel chickens and 238 wild birds collected in New Jersey from May-December 2000. Ten mallard ducks (Aftus plat!lrlry~fchos) experimentally infected with West Nile virus and six uninfected controls were also tested. The ELISA proved specific in detecting WNV antibodies in 9/10 chickens and 414 wild birds previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…Polyclonal and monoclonal antibodies to the NS1 protein have identified type-, complex-, and flavivirus-specific epitopes [34], which are mainly conformation dependant but are not virus neutralising. The NS1 protein of WNV has also been demonstrated to be antigenic and has been used as a diagnostic reagent in antibody capture ELISA procedures [44].…”
Section: The Envelope Protein Ementioning
confidence: 99%
“…Polyclonal and monoclonal antibodies to the NS1 protein have identified type-, complex-, and flavivirus-specific epitopes [34], which are mainly conformation dependant but are not virus neutralising. The NS1 protein of WNV has also been demonstrated to be antigenic and has been used as a diagnostic reagent in antibody capture ELISA procedures [44].…”
Section: The Envelope Protein Ementioning
confidence: 99%
“…Blood for antibody testing (0.2 mL) was dispensed immediately into individually labeled tubes containing 1.8 mL phosphate-buffered saline diluent with 0.75% bovine serum albumin, 28 kept on ice packs, and processed at the Orange County laboratory using a blocking enzyme-linked immunosorbent assay (ELISA) with a baculovirus-Kunjin epitope NS1 recombinant antigen and specific anti-West Nile NS1 monoclonal antibody 3.1112G, 29,30 on heat-inactivated sera. In addition, from August through October 2008, blood (~0.05 mL) from 84 free-ranging birds was added to individually labeled vials containing 1-mL Eagle's Minimum Essential Medium, frozen in the field on dry ice, and evaluated for the presence of active WNV in free-ranging birds by RT-PCR and inoculated Vero and porcine stable equine kidney (PSEK) cell cultures .…”
mentioning
confidence: 99%
“…Gibbs et al (2005) observed mononuclear leukocytosis and epicarditis/myocarditis most consistently in WNV-positive blue jays. Two other pathology studies found differing results with significant histologic lesions in freeranging crows in many organs except mild lesions in the brain (Steele et al, 2000) and more severe brain lesions in Purkinje cells and their dendrites as well as in neurons and glial cells (Jozan et al, 2003). Raptors exhibit WNV lesions in common with corvids, including myocardial inflammation and necrosis, lymphoplasmacytic encephalitis, and hepatitis (Ellis et al, 2007).…”
Section: Discussionmentioning
confidence: 99%